Clinical epidemiology of congenital heart disease in Nigerian children, 2012–2017. Issue 16 (19th September 2018) - Ekure, Ekanem N.; Kalu, Nnenna; Sokunbi, Ogochukwu J.; Kruszka, Paul; Olusegun‐Joseph, Akinsanya D.; Ikebudu, Desmond; Bala, David; Muenke, Maximilian; Adeyemo, Adebowale
Abstract : Background: Congenital heart diseases (CHDs) affect 1% of newborns and are a significant cause of morbidity and mortality in children. We present the clinical epidemiology of CHD as seen in a large university medical center in Nigeria. Methods: Participants were 767 children with echocardiographically confirmed CHD seen over a 5‐year period at the Lagos University Teaching Hospital, Nigeria. Results: Clinical presentation was often late with just over half (58.1%) presenting in infancy. The male:female distribution was 1:1. The predominant types of cardiac lesion seen were septal defects (43%), conotruncal defects (23.7%), atrioventricular septal defects (9.8%), and right ventricular outflow tract obstruction (7.3%). Cyanotic CHD was seen in 28.4% of cases and the single most common cyanotic CHD was Tetralogy of Fallot (13.4%). Children with cyanotic CHD were older ( p = .002), had more severe lesions ( p < .0001) and were more likely to have cardiac intervention ( p < .0001). Extracardiac malformations were present in nearly one‐third of the children. Syndromes associated with CHD were identified in 15.5% of the children and included Down syndrome (11.9%), congenital rubella syndrome (1.0%), and Marfan syndrome (0.7%). Conclusions: This study is a large case series of CHD from a single site in sub‐Saharan Africa utilizing clinical, epidemiological, and developmental considerations. It provides a rich and up‐to‐date description of the clinical epidemiology of CHD in Nigerian children while yielding data that could be useful for designing genetic, molecular, and biomarker studies.